2014
DOI: 10.1111/iju.12393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of testosterone fractions between Framingham Heart Study participants and Japanese participants

Abstract: Abbreviations & Acronyms aFT = analog-based free testosterone AMS = Aging Questionnaire ASA = American Society of Andrology cFT = calculated free testosterone CI = confidence interval CV = coefficient of variation Objectives: To determine testosterone fractions in Japanese men and to compare these values with those of Framingham Heart Study participants. Methods: We enrolled 498 healthy Japanese men. Total testosterone was assayed by liquid chromatography tandem mass spectrometry, sex hormone-binding globulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Furthermore, multivariate analysis revealed that lowered TT, tentatively defined as <4 ng/mL, was the only detection marker for MetS. It is controversial whether serum TT levels decrease with aging or not [25][26][27][28][29]. As an example, a slight decrease of TT with aging was observed in the Framingham Heart Study [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, multivariate analysis revealed that lowered TT, tentatively defined as <4 ng/mL, was the only detection marker for MetS. It is controversial whether serum TT levels decrease with aging or not [25][26][27][28][29]. As an example, a slight decrease of TT with aging was observed in the Framingham Heart Study [25].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a slight decrease of TT with aging was observed in the Framingham Heart Study [25]. However, recent large scale investigations targeting healthy Chinese men [26] and healthy Japanese men [27][28][29] have repeatedly concluded that the serum levels of TT were unchanged by aging. According to one report, the differences that have been observed may be owing to racial differences but not to a difference in the assay method [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among male advanced cancer patients with cachexia, up to 70% of patients reportedly have hypogonadism defined as low serum testosterone levels which could induce many cancer -related symptoms including cachexia itself (1,2,6). Testosterone functions to keep males healthy and decreases gradually with age (7,8). Testosterone increases bone mineral density and muscle mass (9,10), improves mental function and cognitive impairment (11,12), decrease lower urinary tract symptoms and nocturia (13,14), and maintains cardiovascular health (15).…”
Section: Discussionmentioning
confidence: 99%